2000
DOI: 10.1007/s004080000006
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia Causes an Increase in Antioxidant Enzyme Activity in Adult and Fetal Rat Type II Pneumocytes

Abstract: It is well known that exposure to hyperoxia results in lung inflammation and damage, which leads to the development of chronic lung disease. Previous studies have shown increased activities of antioxidant enzymes (AOE) in lung tissue from animals exposed to hyperoxia. We propose the hypothesis that the fetal type II pneumocytes (TIIP) would be resistant to oxygen toxicity by virtue of increasing AOE activity on exposure to hyperoxia. The aim of this study was to measure the activities of catalase, glutathione … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 22 publications
0
30
1
Order By: Relevance
“…Consequentially, an increase in antioxidant activities is a common occurrence during oxidative stress (Bhandari et al 2000). To verify whether mitochondrial antioxidant activities were similarly increased, SOD and CAT activities were measured.…”
Section: Resultsmentioning
confidence: 99%
“…Consequentially, an increase in antioxidant activities is a common occurrence during oxidative stress (Bhandari et al 2000). To verify whether mitochondrial antioxidant activities were similarly increased, SOD and CAT activities were measured.…”
Section: Resultsmentioning
confidence: 99%
“…A second possibility is that hyperoxia sensitizes or primes host cells to apoptosis-triggering stimuli that are elaborated by Legionella infection. Hyperoxia may affect a variety of host biological systems, such as antioxidant enzymes (43) and cytokine production (28), through excessive production of reactive oxygen species. Several investigators have reported that hyperoxia up-regulates TNF-␣ gene and protein expression, especially after triggering stimuli (35,36,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we showed that although glutathione oxidation in response to hyperoxia exposure was present in both sexes, the magnitude of change was significantly greater in the lungs of female, as compared with male, pups. This, we believe, relates to the increased H 2 O 2 content in female newborn pup lungs exposed to 100% O 2 because in its presence glutathione peroxidase activity increases (34).…”
Section: Articlesmentioning
confidence: 87%